VD_FINDINFO HC / 2024 / 687 vom 9. September 2024 - VD Tribunal cantonal (2024)
DÉCISION D'IRRECEVABILITÉ, FORMALISME EXCESSIF, PRINCIPE DE LA BONNE FOI | 29 al. 1 Cst., 202 CPC (CH), 209 CPC (CH), 221 CPC (CH)